Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1017/s0954579411000678
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' physical abusiveness in a context of violence: Effects on the mother–child relationship

Abstract: The purpose of this study was to investigate the effects of mothers' physical abusiveness on the quality of the mother-child relationship, and note how it further varied by their exposure to interparental violence (IPV). The sample consisted of 232 clinic-referred children, aged 2 to 7 years, and their biological mothers. Slightly more than a quarter of the children (N = 63, 27.2%) had been physically abused by their mothers; approximately half of these children also had a history of exposure to IPV (N = 34, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…Likewise, there is research which suggests that, in homes affected by IPV, there is a greater propensity for severe disciplinary action and aversive interactions with children [33,35,36]. Mothers often face difficulties in establishing limits for their children, resulting in a situation where children are overprotected or, in contrast, situations of negligence and abandonment [32].…”
Section: Violence Experienced By Children In the Context Of Ipvmentioning
confidence: 99%
“…Likewise, there is research which suggests that, in homes affected by IPV, there is a greater propensity for severe disciplinary action and aversive interactions with children [33,35,36]. Mothers often face difficulties in establishing limits for their children, resulting in a situation where children are overprotected or, in contrast, situations of negligence and abandonment [32].…”
Section: Violence Experienced By Children In the Context Of Ipvmentioning
confidence: 99%
“…Among aspects of emotional availability to young children, maternal sensitivity (appropriate emotional expression and response to the child’s expressions) and nonintrusiveness (emotional presence without overriding the child’s needs) are highly relevant to mothers’ appropriate understanding of emotional cues from their infants (Ainsworth, 1979). Difficulties in understanding infant emotions can be associated with low emotional availability behaviors such as intrusive or insensitive parenting, which can lead to negative mother-infant relationships and insecure infant-mother attachment (Belsky, 1993; Cicchetti & Toth, 2005; Killeen & Teti, 2012; Timmer, Thompson, Culver, Urquiza, & Altenhofen, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Bronfenbrenner's () model includes the chronosystem, noting that events and transitions influence the relations between other aspects of the ecology over time. The dyads in the current study look most similar to those in a study of high‐risk (e.g., child maltreatment, IPV, maternal substance use), low‐SES dyads referred for parent–child therapeutic treatment for child disruptive behavior problems (Timmer, Thompson, Culver, Urquiza, & Altenhofen, ). Despite the child age difference in the samples (ages 2–7 years in the Timmer et al study), the EA scores were quite similar, and low.…”
Section: Discussionmentioning
confidence: 52%
“…When looking at maternal history, it is observed that the practice of these tactics goes beyond the parent–child relationship indicating a possible transgenerational component in this behavior, as 78.4% of the mothers reported at least one experience of physical assault by their parents during their own childhood. Given the early comparison of our sample to a clinical risk sample (Timmer et al., ), we noted a concern that some of these dyads may continue to experience asynchronous mother–child interactions, resulting in problems in children's behavioral regulation.…”
Section: Discussionmentioning
confidence: 99%